PRAKTIK WANPRESTASI PADA PERJANJIAN JUAL BELI MOTOR BEKAS DI DUSUN MENGANTO KABUPATEN JOMBANG - Fuddin, Afii; Asi Islami, Trinah (Magister Ilmu Hukum, Universitas Wisnuwardhana Malang, 2024)
The problem of this research is the phenomenon of nonpayment, where the seller acts unilaterally because the seller does not fulfill his obligations in full. The purpose of this study is to identify negligent practices in the sale and purchase of used motorcycles in Menganto Hamlet, Menganto Village, Mojowarno District, Jombang Regency according to the Sharia Economic Law Association. This research uses the theory of buying and selling contracts based on an act by which one or more people bind themselves to one or more other people and do not conflict with existing regulations. The type of research used in this research is juridical-empirical. The task is to study the law and its application in society and look for facts contained in society, legal entities or government agencies. The results and conclusions of the research show that the seller in this study acted negligently by not doing what was promised, doing what was required but not as promised, and doing what should not be done in the contract. Keywords: Default of sale and purchase agreement, KHES, Civil Code